Performance Analysis and Portfolio Optimization Method on Stock Market INvestment: A Study of PT Telekomunikasi Indonesia Pension Fund Year 2006-2011 (The Indonesian Journal of Business Administration, 2013)
PT Telekomunikasi Indonesia Tbk., Pension Fund (DAPENTEL) during year 2006 to 2011 was cannot meet the targets of Return on Investment (ROI) which was set in each early year by its management. This is because most of its funds invested on the stock market investment where the target of investment return is not achieved. The DAPENTEL method of stock investing by external investment manager will give additional investment cost and were not give optimal investment return for the company since most of the year 2006 -2011 resulting in negative value of ROI. Motivated by these problems I show that stock investment performance analysis by using valuation of the Holding Period Return (HPR), stock risk analysis, and risk premium analysis and selected stocks which are have higher performance than the market as a next year stock investment portfolio. Last, considering their performance value and their risk value as a weighting method will give a better investment result for DAPENTEL Return on Investment (ROI).Â Keywords: pensions fund, investments, stocks, ROI, HPR, Risk, Risk Premium, and Stock weighting